THE EFFECT OF VISUAL MERCHANDISING ON CONSUMER IMPULSE BUYING BEHAVIOR AT THE EXECUTIVE STORE MANADO - Sumeisey, Gisela Maria (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
The marketplace nowadays is having tight competition between stores or companies which is a new comer or the long-time one. Stores or companies have to utilize strategies especially merchandising tools in order to attract consumer’s attention to survive in the competition. The strategy of visual merchandising is often used by stores or companies to stimulate consumer’s want towards their product. The aim of this study is to analyze the effects of visual merchandising on consumer impulse buying behavior with particular emphasis on these variables: window displays, form displays, floor merchandising, and promotional signage uses quantitative method. The data used in this research is primary data obtain through questionnaire. The population observed is people in Manado who buy from The Executive store as many as 100 respondents. Results and conclusion are from all variables of visual merchandising such as: window displays, form displays, floor merchandising, and promotional signage, not all variables have a significant influence on consumer impulse buying behavior. Floor merchandising has no significant influence and the most significant influence comes from promotional signage. The recommendation for the store is maintains and improves the promotional signage that can turn the window shopper into real buyer. Keywords: window display, promotional signage